EFFECT OF A BEDSIDE HANDOVER EDUCATIONAL INTERVENTION ON PATIENTS SATISFACTION IN MMC KUNINGAN HOSPITAL JAKARTA - Lister Friska Manalu; Blacius Dedi; Wilhelmus Hary (Alta Dharma Publisher, 2019)
Successful implementation of bedside handovers depends on communication, where communication is one of the predictors of patient satisfaction. The purpose of this study was to determine the effect of bedside handover educational intervention on patient satisfaction. A Quasi-experimental study design, pre-test and posttest with nonequivalent control group were applied in this study. Respondents obtained as many as 118 for the intervention group and 30 respondents for the control group. A paired t- test, an independent t-test, chi-squared test and a SEM (structural equation model) were used to analyze data. The results of test hypotheses shows five of the seven independent variables have significant effect on patient satisfaction and two insignificant effect on patient satisfaction; bedside handover educational intervention t = 3.64, implementation of bedside handovers t = 3.66, bedside handover perceived by patients t = 4.4, age t = 7.1 and education level variables t = 3.55. Two insignificant independent variables that not have effect on patient satisfaction were gender t = -3.34 and patient health status t = -2.07. To achieve patient satisfaction, bedside handover can be applied as one of the handover methods in the inpatient care room. Keywords: bedside handover, patient satisfaction, education intervention, communication